Training workbook on water safety plans for urban systems. (World Health Organization, Western Pacific Region, 2008)
Every year, thousands of deaths due to diarrhea, cholera, typhoid and other gastrointestinal diseases have been attributed to poor water, sanitation and hygiene not just in this region but globally. Diarrheal diseases could be avoided if water suppliers would ensure the safety of drinking water from source to consumer. Guided by the national drinking water regulations, the health-based targets of maximum allowable concentration for microbiological, chemical, physical and radiological parameters in drinking water could be achieved through the application of the multiple barrier approach to risk.